2014
DOI: 10.1016/j.athoracsur.2013.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Acute Kidney Injury as a Severity Index for Thirty-Day Readmission After Cardiac Surgery

Abstract: Background Of patients undergoing cardiac surgery in the United States, 15–20% are re-hospitalized within 30-days. Current models to predict readmission have not evaluated the association between severity of post-operative acute kidney injury (AKI) and 30-day readmissions. Methods We collected data from 2,209 consecutive patients who underwent either coronary artery bypass (CABG) or valve surgery at seven member hospitals of the Northern New England Cardiovascular Disease Study Group Cardiac Surgery Registry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 20 publications
6
48
0
4
Order By: Relevance
“…This definition appears to be very strict, but recent literature indicates that AKI even in stage I carries a high impact on short- and long-term prognosis of patients. Patients experiencing AKI have a higher risk of mortality, readmission rates and a higher risk for developing heart failure as compared to patients without AKI [4, 5, 22, 23, 26, 27]. Using SCr or drop in urine volume to diagnose AKI is problematic, because both markers develop after tubular damage has occurred [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This definition appears to be very strict, but recent literature indicates that AKI even in stage I carries a high impact on short- and long-term prognosis of patients. Patients experiencing AKI have a higher risk of mortality, readmission rates and a higher risk for developing heart failure as compared to patients without AKI [4, 5, 22, 23, 26, 27]. Using SCr or drop in urine volume to diagnose AKI is problematic, because both markers develop after tubular damage has occurred [7].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of [TIMP-2*IGFBP7] before surgery was not helpful to predict AKI, neither alone nor in combination with [TIMP-2*IGFBP7] values at ICU admission. AKI is a common complication after cardiac surgery with an incidence between 20-50% in patients undergoing cardiac surgery [2, 3, 22-25]. Stage I of AKI according to most recent guidelines is defined as a rise in SCr of ≥0.3mg/dl within 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…AKI in patients with heart failure or following cardiac surgery is shown to be associated with readmission (20,21). With heightening societal and political interest in cost-effective healthcare delivery, AKI at the time of critical care may be a marker for critical illness survivors who are at high risk for subsequent adverse events.…”
mentioning
confidence: 99%
“…Postoperative AKI is associated with an increased risk of readmission, incidence, and progression of CKD, as well as poor long-term survival. 121,[125][126][127][128] Coca et al 126 recently showed that urinary biomarkers of tubular injury measured in the early postoperative period are NOTE. The Cleveland Clinic Score 96 was designed to predict RRT after adult surgery: a score of 0 carried an incidence of RRT of 0.13%, a score of 4 had an incidence of RRT of 2.3%, a score of 6 had an incidence of RRT of 8.0%, and a score of 10 had an incidence of RRT of 19.6%.…”
Section: Outcomes Of Postoperative Akimentioning
confidence: 98%